Poporodní netraumatická zlomenina krízové kosti: kazuistika a biomechanické poznámky - Druga, R; Drugová, B (Ceska gynekologie, 2008)
OBJECTIVE: A case report describing postpartal nontraumatic sacral fracture. DESIGN: A case report and biomechanical commment. SETTING: Institute of anatomy, 2nd Medical faculty, Charles University at Prague. SUMMARY: Nontrauma--related stress fractures of the sacrum are rare complications of the pregnancy and postpartal period. We report a new case of nontrauma-related postpartal sacral fracture. A 36-year-old woman after second delivery presented symptoms of left L 5 radiculopathy. MRI of the lumbar spine and pelvis demonstrated a vertical fracture through the left sacral wing, paralel to the left sacroiliac joint (type Denis I). Fracture was surrounded by prominent bone marrow oedema. Biomechanical factors contributing to the stress fractures of the pelvic girdle in pregnancy and post partum are discussed.
Keywords: fraktury páteře; Spinal Fractures; Obstetric Labor Complications; Fractures, Stress; Sacrum; ženské pohlaví; dospělí; křížová kost; Humans; stresové fraktury; Adult; Female; Pregnancy; komplikace porodu; Puerperal Disorders; poruchy v puerperiu; těhotenství; lidé